The Evolution of the Role of Mass Media in Wars – Media as a Tool, a Threat and a Side of the War - Derlatka, Katarzyna E. (Faces of War, 2025)
Released information can lead to the outbreak of war, such as ‘The Ems Telegram’. It can also cause changes in the actions of the ‘great and the small’ of this world, influence the perception of reality and lead to a reversal of events. The examples of the media’s involvement in the history of wars described in this article demonstrate its use by conflicting parties as an instrument of warfare. Furthermore, they also make it clear that the media can be a threat and even a war party. During war, it is necessary to control the media space, understand the role of the media, pay attention to their presence in war, their technological capabilities, and their power to influence audiences and developments. Skilful and planned use of the media for political and military purposes can influence the success of operations.